Studi Epidemiologi Kualitas Hidup Penderita Paska Stroke di RSUD Propinsi Nusa Tenggara Barat - Ilsa Hunaifi; Pujiarohman Pujiarohman (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2019)
troke is a leading cause of mortality and morbidity in Indonesia.  Post stroke patients has a higher disability hence results in poor quality of life compared with normal population. In Indonesia, studies related to the quality of life of post-stroke patients are scarce, so studies are required to explore the quality of life of post-stroke patients, particularly in West Nusa Tenggara. Aim of this study is to determine the epidemiology of quality of life for post-stroke patients in West Nusa Tenggara. Methods of this study is An Observational with cross-sectional design was performed in population of post-stroke patients admitted to West Nusa Tenggara General Hospital. The quality of life of post stroke patient was evaluated with SSQOL (Stroke Specific Quality of Life) questionnaire. The collected data was analyzed by the appropriate test. Result of this study is the average age of subject is 60.33±10.68 years. Hypertension is a major risk factor of stroke. The average SSQOL score is 177.02±45.75. SSQOL assesses 4 dimension are physical, functional, psychological and social health. Based on the physical dimension, the average score is 17.00, the functional dimension, the average score is 14.91, the psychological dimension, the average score is 13.17 and the social health dimension  the average score is 13.44.  The quality of life for post-stroke patients in West Nusa Tenggara General Hospital is good.